Remote patient management in peritoneal dialysis - Ronco, Claudio 1951-; Crepaldi, Carlo; Rosner, Mitchell H. (Basel : Karger, 2019)
Telemedicine and remote patient monitoring are innovative tools to provide remote transmission, interpretation, and storage of data for review by the care team. These tools allow for accurate home monitoring of patients enabling the team to improve care through prevention and early identification of problems. This book is structured into four main parts. The first describes the evolution of peritoneal dialysis and related technology. The second part summarizes current unmet clinical needs reported by patients and care teams, the need for innovation in the field, and the technical and clinical issues involved with the modern management of peritoneal dialysis. The third section presents the operational characteristics of the new information communication technology system and, in detail, the features of the Sharesource platform. Finally, a series of field experiences by expert users are reported to describe the benefits and the potential applications of remote patient monitoring in the future. Telemedicine and remote patient monitoring have proven to be useful in the care of patients on peritoneal dialysis. The scope of this publication, therefore, is to present the experiences of clinical key opinion leaders who have been using the application.
Keywords: DIÁLISIS PERITONEAL; TELEMEDICINA; MONITOREO FISIOLÓGICO